Analisa Laju Konsumsi Bahan Bakar Gas LPG pada Insinerator Limbah Medis Dual Chamber dengan Variasi Durasi Waktu Injeksi Oksigen - Sakya Sanatana, I Ketut; Suprapta Winaya, I Nyoman; Arya Darma, I Wayan; Angga Yuda Pratama, I Putu; Tenaya, I Gusti Ngurah Putu (Teknik Desain Mekanika, 2023)
Abstractt Medical waste falls under the category of hazardous waste, known as B3 waste, which poses a high level of danger and potential risks to health and the environment. Therefore, the handling of medical waste must be taken seriously and diligently. One effective method for managing medical waste, especially hazardous B3 waste, is through the process of incineration using a device called an incinerator. In this method, medical waste is treated through high-temperature combustion, aiming to achieve optimal waste reduction. In this study, oxygen injection was introduced into the second combustion chamber of a dualchamber medical waste incinerator, with varying durations of oxygen injection. The objective was to determine the rate of LPG gas fuel consumption during the combustion process. The research conducted three variations of oxygen injection duration: 2 minutes, 3 minutes, and 4 minutes, using 1 kg of medical waste. The incineration process was carried out at a temperature of 800°C in chamber 1 and 1000°C in chamber 2. The results of the study indicated that as the duration of oxygen injection increased, the supply of oxygen entering the second combustion chamber also increased. This resulted in a decrease in the rate of gas fuel consumption. The most optimal rate of gas fuel consumption was found in the variation with a 4-minute duration of oxygen injection, which amounted to 6.17 kg/hour. Keywords: Dual Chamber Fixed Grate Incinerator, Oxy-fuel.